Upaya meningkatkan kreativitas peseta didik dalam pembelajaran seni rupa terapan melalui penerapan teknik cap pelepah pisang kelas II SDN Karangtengah - Yevira Yuliana; Riza Fatimah Zahrah; Deni Chandra (IKIP Siliwangi, 2026)
This study aims to improve students' writing skills through the implementation of the Outdoor Learning model in Indonesian language learning. The research method used is classroom action research (CAR), which consists of planning, action, observation, and reflection in each cycle. The subjects of this study were 25 students, consisting of 15 female and 10 male students. Based on the research results, students had difficulty writing poetry due to their limited writing skills. They struggled to find ideas to turn into poems. The results of this study indicate that students' writing skills improved through the use of the Outdoor Learning model. In the first cycle, the average score was 63.04%, with 15 students reaching the minimum mastery criteria and 10 students not yet meeting it, amounting to 40% and categorized as high. In the second cycle, the average score increased to 71.33%, with 18 students reaching mastery and 7 students not yet meeting it, amounting to 28%, and categorized as very high. Keywords: Writing Skills, Outdoor Learning Method, Indonesian Language Learning